Makna Simbolik Kehidupan Penyair dalam Puisi “Capungku” Karya Zawawi Imron - Ulum Janah; Anna Anganita Theresia Latumeten (Faculty of Letters Universitas Balikpapan, 2023)
Poetry is a form of literature that is not only in the form of beautiful words, but also has a deeper meaning for the poet himself (the poet). Poetry becomes an expression of the contents of the heart that describes the poet's life and experiences. Through a qualitative method with a semiotic approach, this study tries to reveal the poet's life by determining the syntagmatic and paradigmatic of the Poetry